Katowicki „Bal manekinów” (PDF 1,95 MB) (Książnica Śląska, 2025)
The article describes the Polish first performance of Bruno Jasieński’splay The Mannequins’ Ball (20th July 1957), which was one of themost important performances of the Silesian Theater in Katowiceunder the direction of Józef Wyszomirski, and the diploma work and debut of the outstanding playwright Jerzy Jarocki. The author presents the history of the work’s creation, the history of the Polish firstperformance and places it in the socio-political life of Poland and theKatowice Voivodeship at that time. The voices of the critics illustratethe extraordinary and unexpected social resonance of this importantperformance in the history of the Silesian Theater.